Vitamin K2 Dependent Matrix Gla Protein Relating to Abdominal Aortic Aneurysm and Overall Mortality: A Combined Case Control and Cohort Study. (August 2021) - Kristensen, Joachim S.S.; Melholt, Lars; Kristensen, Katrine L.; Dahl, Marie; Lindholt, Jes S.
Abstract : Objective: Inactivation of matrix Gla protein (MGP), using vitamin K antagonists or vitamin K deficiency results in increased vascular calcification, which has been associated with increased risk of symptomatic or ruptured abdominal aortic aneurysm (AAA). Insufficient activation of MGP leads to increased levels of undercarboxylated forms of MGP, measured as a dephosphorylated, undercarboxylated MGP (dp-ucMGP) in plasma. This study aimed to investigate whether the level of inactivated MGP influenced the risk of having an AAA, the risk of AAA progression, and overall mortality. Methods: This combined case control and cohort study was based on data from the randomised, clinically controlled Viborg Vascular (VIVA) screening trial. Cases ( n = 487) with an AAA and controls ( n = 189) with neither peripheral artery disease nor AAA, had their plasma quantified for dp-ucMGP. Plasma levels were compared with the presence of an AAA, AAA growth rate, need for repair, and overall mortality. dp-ucMGP was divided into tertiles in regression analyses. Results: The plasma levels of dp-ucMGP were higher for AAA cases compared with controls (median of 517 pmol/L vs. 495 pmol/L, p = .036). Adjusted analyses regarding dp-ucMGP being predictive of AAA, AAA growth rate, and need for repair all failed to show correlation. Overall mortality for AAA cases exhibited a significant association for the third tertile of dp-ucMGP with a hazard ratio of 2.55 (95% CI 1.29 – 5.05) compared with the first tertile. Overall mortality for controls was not correlated with dp-ucMGP plasma levels. Conclusion: dp-ucMGP did not correlate with the risk of having an AAA, AAA growth rate, or risk of surgery. For people with an AAA, dp-ucMGP was correlated with an increased mortality risk for the highest tertile of dp-ucMGP. This could suggest a role for prophylactic measures with vitamin K2 supplements to people at risk of AAA.